Assessing the Determinants of Financial Performance of Commercial Banks in Selected Sub-Saharan African Countries, 2001-2023 - Otayokhe, Esther Yemi Otayokhe; Ajiboye, Thomas Wale Ajiboye; Jimba, Kareem Isiaka Jimba; Ibitoye, Olusola Anthony Ibitoye; Ogundele, Abiodun Thomas Ogundele (African Journal of Stability and Development (AJSD), 2025)
This study investigates the determinants of financial performance of commercial banks in selected Sub-Saharan African countries, specifically Nigeria, Cameroon, Kenya, and South Africa, from 2001 to 2023. The banking sector plays a crucial role in economic growth, yet its profitability remains low despite various reforms. Key variables include the bank’s internal factors on financial performance: management efficiency, capital strength, asset quality, liquidity management, market share, banking sector development, GDP growth, inflation rate, interest rate spread, and real exchange rate. This research aims to identify and compare the internal (bank-specific), industry-level, and macroeconomic factors influencing bank profitability. Utilising a quantitative approach, the study employs a dynamic panel data methodology, specifically the Generalised Method of Moments (GMM), to analsze data from 20 selected banks across the four countries. The findings provide insights into the unique challenges and opportunities faced by banks in the region, contributing to the existing literature on bank profitability and offering practical implications for policymakers and banking stakeholders. The study recommends that commercial banks should incorporate fintech adoption and digital banking metrics to assess their impact on bank profitability and operational efficiency in Sub-Saharan Africa. There is a need for a comparative analysis across different banking regulatory environments that could provide deeper insights into how policy reforms influence financial performance in the region.